2021
DOI: 10.1002/ppul.25566
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric flexible bronchoscopy in the intensive care unit: A multicenter study

Abstract: Introduction: Flexible bronchoscopy (FB) is frequently used for assessment and treatment of patients with respiratory diseases. Our aim was to investigate the contribution of FB to diagnosis and therapy in children admitted to the intensive care units (ICU) and to evaluate the safety of FB in this vulnerable population.Methods: Children less than 18 years of age who underwent FB in the five neonatal and pediatric ICUs in Istanbul between July 1st, 2015 and July 1st, 2020 were included to the study. Demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
4
0
2
Order By: Relevance
“…Our study reported that FB revealed at least one positive finding in 95.92% of the patients admitted to NICU. Previous research reported that 79–98% of patients in the NICU have at least one abnormality detected using FB ( 16 , 19 , 20 ). Herein, the high rate of abnormal findings may be secondary to infants’ reluctance to perform early FB, resulting in severe and persistent symptoms that precede FB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study reported that FB revealed at least one positive finding in 95.92% of the patients admitted to NICU. Previous research reported that 79–98% of patients in the NICU have at least one abnormality detected using FB ( 16 , 19 , 20 ). Herein, the high rate of abnormal findings may be secondary to infants’ reluctance to perform early FB, resulting in severe and persistent symptoms that precede FB.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that laryngomalacia was the most common cause of upper airway obstruction, recurrent dyspnea, stridor, and hoarseness in newborns. In a retrospective report of 196 bronchoscopies, it was documented that airway malacia was found in 47.4% of cases ( 19 ). In addition, a 60–70% incidence of laryngomalacia was reported in neonates and children with stridor ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tekrarlayan alt solunum yolu enfeksiyonları (ASYE) (1 yıllık dönemde en az iki ,yaşam boyunca en az üç pnömoni epizodu), kronik öksürük (4 haftadan uzun süren öksürük), persistan hışıltı (astım tedavisine yanıt vermeyen olgularda devam eden hışıltı), stridor, persistan atelektazi, yapısal anomali şüphesi endikasyonları ve altta yatan bilinen hastalığa yönelik BAL alınması amacı ile FB gerçekleştirildi (10)(11)(12)(13).…”
Section: Gereç Ve Yöntemunclassified
“…BAL örneği steril bir numune kabına aktarıldı. 10000 kob/ml üzerindeki üreme mikrobiyolojik olarak anlamlı kabul edildi (10)." FB ile ilgili komplikasyonlar minör ve major olarak gruplandırılmıştır (14).…”
Section: Gereç Ve Yöntemunclassified